Constancy of the bioactivities of propolis samples collected on the same apiary over four years - Freitas, Ana Sofia; Cunha, Ana; Cardoso, Susana M.; Oliveira, Rui; Almeida-Aguiar, Cristina (Food research international, 2019)
Natural products, like propolis, have been subject of interest by several industries mainly due to their biological activities. However, besides being produced in low amounts propolis has a great variability in terms of chemical composition and bioactivities' profiles, constituting a problem for the development of propolis-based products and for its acceptance by the medical community. The aim of this work relates to the study of the bioactivities, in particular the antioxidant and the antimicrobial properties, as well as the chemical characterization of Portuguese propolis samples collected in an apiary sited at Gerês (G) along four consecutive years. Ethanol extracts of the four propolis samples (G.EEs) display antimicrobial activity, especially against Gram-positive spore forming bacteria. Antioxidant activity, evaluated by three different in vitro assays, was confirmed in vivo by flow cytometry using Saccharomyces cerevisiae as eukaryotic cell model. Cells incubated with G.EEs prior to H2O2 incubation, or incubated with G.EEs and H2O2 simultaneously, display higher viability than cells incubated only with H2O2, suggesting that G.EEs protect yeast cells against induced oxidative stress. All tested propolis samples exhibit very similar antimicrobial and antioxidant activities. Chemical analysis of G.EEs revealed no significant differences in terms of phenolic profiles, namely in the compounds to which propolis bioactivities are ascribed, thus supporting the more constant behavior evidenced by these propolis samples. This work highlights the valuable properties of this bee product and reveals a constancy of bioactivities in a Portuguese propolis sample over four years, raising awareness to the potentialities of this natural product often regarded as a beekeeping waste. [Display omitted] •Antibacterial activity is shown by all four propolis samples.•Specific spectrum of action was found against gram-positive spore forming bacteria.•All propolis samples show good antioxidant activity both in vitro and in vivo.•Propolis samples exhibit similar biological activities over four years.•Similarities in chemical profiles confirm the constancy of bioactivities.